Financial instrument pricing using C++ - Duffy, Daniel J. (Hoboken, NJ : John Wiley, 2004)
This book has several features that allow developers to write robust, flexible and extensible software systems. The book is an ANSI/ISO standard, fully object-oriented and interfaces with many third-party applications. It has support for templates and generic programming, massive reusability using templates (?write once?) and support for legacy C applications. In this book, author Daniel J. Duffy brings C++ to the next level by applying it to the design and implementation of classes, libraries and applications for option and derivative pricing models.
Includes bibliographical references and index.
08/05/13
Loans
Keywords: C++ (Computer program language); Financial engineering